Black ties only?: Ethnic business networks, intermediaries, and African American retail entrepreneurship - Rauch, James E. (Networks and Markets, 2001)
Networks and Markets argues that economists' knowledge of markets and sociologists' rich understanding of networks can and should be combined. Together they can help us achieve a more coherent view of economic life, where transactions follow both the logic of economic incentives and the established channels of personal relationships. Market exchange is impersonal, episodic, and carried out at arm's length. All that matters is how much the seller is asking, and how much the buyer is offering. An economic network, by contrast, is based upon more personalized and enduring relationships between people tied together by more than just price. Networks and Markets focuses on how the two concepts relate to each other: Are social networks an essential precondition for successful markets, or do networks arise naturally out of markets, as faceless traders build reputations and gain confidence in each other? The book includes contributions by both sociologists and economists, applying the concepts of markets and networks to concrete empirical phenomena. Among the topics analyzed, the book explains how, in Taiwan, South Korea, and Japan, firms combine into tightly-knit business blocs, how wholesalers in a Marseille fish market earn the loyalty of customers, and how ethnic retailers in the U.S. share valuable market information with other shopkeepers from their ethnic group. A response to each chapter discusses the issue from the standpoint of the other discipline. Sociologists are challenged to go beyond small-scale economic exchange and to integrate their concept of networks into a broader understanding of the economic system as a whole, while economists are challenged to consider the economic implications of network ties, which can be strong or weak, unconditional or highly contingent. This book proves that both economics and sociology provide stronger insights when they study markets and networks as parallel forms of exchange. But it also clarifies the healthy division of labor that remains between the two disciplines. Sociologists are adept at showing how markets are framed by social institutions; economists specialize in explaining how markets perform, taking the social context as a given. Networks and Markets showcases what each discipline does best and reveals where each discipline would do better by borrowing from the other.
Keywords: Business & Economics / Economics / General; Business History and race; Social Science / General; Social Science / Sociology / General